(untitled) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2024)
The article analyzes a set of artistic productions from the city of Mar del Plata (Buenos Aires, Argentina) that thematize aspects linked to the civic-military dictatorship. In this sense, the work recovers experiences located in the public space in the years after the democratic recovery and focuses the study on the project called Esquinas con Memoria of the Mar del Plata te Canta los Cuarenta collective. From this, the question arises: what articulations are built between artistic productions, public space and memories of the dictatorial past? Following this question, the text is structured into three axes of analysis: the mode of organization of the project, the relevance of public space as a setting to deploy actions and the relationship between artistic practice and the memory of State terrorism.